The INkWELL Index of Global Innovation - Ashrafian, Hutan (Ann Glob Health, 2018)
The INkWELL index is introduced as a new global innovation index whereby country-level innovation scores can be associated with country-level wellbeing scores, a standard to reflect the ultimate reward of innovation. It is calculated as a composite of the wellbeing score from a nation with its mean national innovation score from the preceding ‘k’ years. The value of k reflects the time-lag from innovation-to-translation into practice that traditional studies have offered a value for 17 years in healthcare. The INkWELL (or INnovation-k-WELLbeing) index can highlight the most innovation-on-wellbeing countries and also offers the assessment of globalization of innovations. As such, this index will offer a meaningful measure of innovation on its ultimate aim of societal wellbeing.